Periodic Kicking Modulated Topological Phase Transitions in a Generalized Chern Insulator - Yang, Feng-Yun; Zhang, Mei-Yu; Wang, Lin-Cheng (International journal of theoretical physics, 2024)
Topological phase transitions of a generalized two dimensional tight-binding Chern insulator with periodic δ -function kicks applied in x , y and z direction defined by the pseudo spin in the two-band systems, have been studied in this paper. The rich phase diagram characterized by Chern numbers as well as the critical lines in such system have been analyzed. This is an extended study about δ -function periodic kicks on topological systems as profound influences on periodic driven quantum systems.